Tích hợp nội dung giáo dục vì sự phát triển bền vững vào chương trình đào tạo đại học - Phan, Thị Yến Lai (Tạp chí Giáo dục, 2023)
The Sustainable Development Goals (SDGs) are not a choice but a mandatory path for each country. The United Nations has adopted the 2030 Agenda with 17 Sustainable Development Goals, in which education for sustainable development (ESD) is a central goal (SDG4) and an important mean of achieving all the other 16 SDGs. Therefore, integrating ESD into university curricula becomes an urgent task that needs attention. This article systematizes some theories related to the integration of ESD in the curriculum and explores the initiatives of some universities around the world. From there, some solutions are proposed for universities in Vietnam to integrate ESD into their curricula towards the country's sustainable development goals. The results of the article can be a reference for universities in integrating the ESD content into the curriculum.